Nursery Resource Pack Communication, Language and Literacy - Term II - The City School (Lahore : The City School)
This book focuses on developing early reading, writing, and speaking skills. It introduces phonics and simple sentence formation while encouraging the use of basic punctuation. Children expand their vocabulary through descriptive language and interactive activities. The pack uses storytelling, rhymes, and role-play to build confidence in communication and comprehension.
Location: 1B
Keywords: Text- book